An online intervention for 18–25‐year‐old youth whose parents have a mental illness and/or substance use disorder: A pilot randomized controlled trial. Issue 11 (3rd February 2022) - Maybery, Darryl; Reupert, Andrea; Bartholomew, Catherine; Cuff, Rose; Duncan, Zoe; McAuliffe, Caitlin; McLean, Louise; Pettenuzzo, Laura; Swing, Alice; Foster, Kim
Abstract: Aim: Young adults aged 18–25 whose parents have a mental illness or substance use problem can be vulnerable to multiple difficulties in adulthood. There are, however, few available interventions designed for this group. This study evaluated a 6 week online intervention (mi. spot; mental illness: supported, preventative, online, targeted) specifically designed for this population. The intervention aims to improve mental health and wellbeing. Methods: Forty‐one young people, recruited from the community, participated in a two‐arm parallel randomized controlled trial where participants were randomized to mi. spot ( n  = 22) or a wait list control group ( n  = 19). They were assessed at baseline, immediately post intervention and at six weeks post intervention with measures covering depression, anxiety and stress, wellbeing, coping, general self‐efficacy, help seeking and social connectedness. Results: Intervention participants reported significantly improved psychological wellbeing, coping, general self‐efficacy, and a reduction in anxiety. Participants in the control group reported significant improvements in emotional wellbeing and help seeking and a reduction in self‐blame. Conclusion: This pilot controlled trial supported previous findings and shows preliminary evidence that mi.spot is effective for young adults who grew up with parents who have a mental illness or substance use problem. A large‐scale, randomized controlled trial with a diverse group of young people is needed.